A malleable workflow for identifying the issues and indicators that define and measure sustainability in food systems - Springer, Nathaniel P.; Hollander, Allan D.; Huber, Patrick R.; Riggle, Courtney; Tomich, Thomas P. (Frontiers in Sustainable Food Systems, 2022)
A variety of stakeholders are concerned with many issues regarding the sustainability of our complex global food system. Yet navigating and comparing the plethora of issues and indicators across scales, commodities, and regions can be daunting, particularly for different communities of practice with diverse goals, perspectives, and decision-making workflows. This study presents a malleable workflow to help different stakeholder groups identify the issues and indicators that define food system sustainability for their particular use case. By making information used in such workflows semantically-consistent, the output from each unique case can be easily compared and contrasted across domains, contributing to both a deeper and broader understanding of what issues and indicators define a resilient global food system.